2017
DOI: 10.1182/blood-2016-09-693598
|View full text |Cite
|
Sign up to set email alerts
|

How I manage ibrutinib-refractory chronic lymphocytic leukemia

Abstract: The introduction of the Bruton tyrosine kinase (BTK) inhibitor ibrutinib has dramatically changed the management of chronic lymphocytic leukemia (CLL). Although responses have been durable in the majority of patients, relapses do occur, especially in the high-risk patient population. Most relapses occur as the result of acquired mutations in BTK and PLCG2, which may facilitate success with alternative targeted therapies. As outcomes after ibrutinib relapse have been reported to be poor, specific strategies are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
52
0
7

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(61 citation statements)
references
References 32 publications
1
52
0
7
Order By: Relevance
“…Despite recent improvements, the management of progressive disease on BCR inhibitors remains challenging (53). The median survival for patients progressing on ibrutinib with CLL is around 2 years, and even shorter for Richter's transformation (10,15,17).…”
Section: Discussionmentioning
confidence: 99%
“…Despite recent improvements, the management of progressive disease on BCR inhibitors remains challenging (53). The median survival for patients progressing on ibrutinib with CLL is around 2 years, and even shorter for Richter's transformation (10,15,17).…”
Section: Discussionmentioning
confidence: 99%
“…For example, BTK, which phosphorylates and primes DDX41, interacts within multiple other signaling pathways including TOLL like receptor signaling, pre-B cell proliferation and signaling of chemokine receptors in B cell malignancies [67]. Accordingly, the use of a BTK inhibitor, ibrutinib, has been trialed for various lymphoid malignancies, dramatically changing management and outcome for individuals with chronic lymphocytic leukemia in particular [67,68]. STING agonists are currently in the development phase.…”
Section: Future Handling and Treatment Of Ddx41-associated Myeloid Mamentioning
confidence: 99%
“…In a previous review paper, Woyach reported a case of a patient with chronic lymphocytic leukemia (CLL) who experienced similar symptoms to the ones reported here, such as fatigue and night sweats and without actual evidence of disease progression [8]. Woyach goes on then to recommend minimizing temporary holds and using steroids in patients who experience withdrawal symptoms.…”
mentioning
confidence: 99%